Role of Deformation Sand Related Aspects in Super Heavy Region - Kumar, Sunil (My University, 2012)
In view of present day developments in the domain of nuclear physics, it is extremely important & essential to study the nuclear structure and related aspects at the extreme conditions of angular momentum, deformations, orientations, temperature and energies in reference to the developments in theoretical & experimental nuclear physics. The tough challenges in nuclear perspective can be met only by developing and establishing clear understanding of related phenomena on the theoretical front, which could be utilized to plan and implement the predictions through experiments. A number of factors and properties influence the fusion-fission process and hence need to be handled with proper care in order to make meaningful predictions. One such aspect, which plays a significant role in fusion-fission process dynamics, is the role of deformed shapes of target, projectile and decaying fragments. It is therefore, important to account for shapes of target projectile combinations and the subsequent decaying fragments in the domain of nuclear reaction dynamics. Keeping this in mind, we have investigated the role of deformations in 296116 super heavy nuclear system formed in 48Ca+248Cm reaction over a wide range of incident energy. The Dynamical Cluster Decay Model (DCM), with deformations up to quadrupole deformations, is used to calculate the fusion evaporation residue cross-section for 3n emission in a hot fusion reaction at various incident energies, taking proton magic number Z=126 and N=184 for super heavy region. The DCM based calculations give good description of measured fusion excitation function, σER(=σ3n) as a function of compound nucleus excitation energy ECN, within one parameter fitting, the neck length ΔR (ECN). Some interesting results related to fragmentation behavior and its dependence on nuclear deformations are taken into account for 296116 nuclear system. The possible implications in reference to temperature and angular momentum effects are addressed in this work.
M.Sc. (Physics)
Keywords: Super Heavy Elements; Deformed Nucle; Preformation Probability